UF/IFAS Standardized Fertilization Recommendations for Agronomic Crops - Rao Mylavarapu; David Wright; Gerald Kidder; C. G. Chambliss (EDIS)
SL-129, a 9-page fact sheet by R. Mylavarapu, D. Wright, G. Kidder, and C. G. Chambliss, presents in abbreviated form the fertilization recommendations for agronomic crops based on soil tests performed by the UF/IFAS Extension Soil Testing Laboratory (ESTL). It contains the basic information from which ESTL soil-test reports and fertilization recommendations are generated. Published by the UF Department of Soil and Water Sciences, June 2007.